(untitled) (KYAMC Journal, 2022)
Background: Neonatal sepsis is defined as a clinical condition of bacteremia with clinical features of infection in the first 28 days of life. Neonatal sepsis is an important cause of neonatal deaths worldwide. If detected early and treated aggressively and appropriately with antibiotics with good supportive care, it can be possible to save a life. Objective: The present study is carried out to overview the clinical and investigations profile, and outcome of neonatal sepsis admitted in a neonatal intensive care unit (NICU). Materials and Methods: This is a retrospective descriptive study. This study included newborns diagnosed with neonatal sepsis admitted to the Neonatal Intensive Care Unit (NICU) of Khwaja Yunus Ali Medical College and Hospital, Sirajgonj from October 2020 to January 2022. The case records of 50 neonatal sepsis. The case records of these newborns were thoroughly studied and recorded for relevant information including detailed history including maternal, clinical evaluation, and available investigation. The outcome was also noted. Results: Among the 50 neonatal sepsis cases early-onset neonatal sepsis was 56%; where mostly preterm (74%) and low birth weight (44%). Clinical presentations were mostly reluctant to feed (70%) associated with other septic features. Septicemia only (36%), pneumonia (14%), neonatal intestinal obstruction (10%) were found as the main pattern of sepsis. Among the cases septic screening profile thrombocytopenia 84%, CRP Positive 78%, leukopenia 58%, anemia 26%, leukocytosis 22%, normal 20%, toxic granules or band form neutrophil 14%, positive blood culture 14% were found. Probable risk factors were found mainly low birth weight (78%) and prematurity (74%); overlapping with many other risk factors. Thirty-six percent were death among sepsis. Conclusion: In the neonatal intensive care unit mostly early-onset neonatal sepsis has been observed in outborn, premature, and Low Birth Weight (LBW) babies presenting with reluctance to feed with associated risk factors; where thrombocytopenia invariably found in sepsis screening and survival rate around sixty-five percent KYAMC Journal Vol. 13, No. 01, April 2022: 32-36